Prevalence and associated factors of acute gastroenteritis in children and adolescents aged from 6 to 17 years old: a cross-sectional study based on the National Health and Nutrition Examination Survey database 1999–2018 - Hailun Cai; Yanyan Shao; Weihao Yu (BMJ Open)
Objective To explore the prevalence of acute gastroenteritis (AGE) and associated factors in children and adolescents in the USA from 1999 to 2018 using nationally representative data.Design A retrospective cross-sectional study.Setting The National Health and Nutrition Examination Survey (NHANES) database.Participants 25 361 children and adolescents aged 6–17 years old.Primary and secondary outcome measures Whether the patient suffered from AGE.Results Totally 1882 suffered from AGE. The overall monthly prevalence of AGE in children and adolescents was 7.69%. From 1999 to 2018, the prevalence of AGE in the USA had been decreasing over time. The decreasing trend was observed in all subgroups, including age, gender, body mass index (BMI), education level, poverty index and eating food at the restaurant. There were two small upticks from 2003 to 2007 and 2013 to 2015. AGE was negatively associated with male compared with female (OR=0.86, 95% CI: 0.73 to 0.99, p=0.035), Mexican American (OR=0.82, 95% CI: 0.70 to 0.97, p=0.018) and non-Hispanic Black (OR=0.80, 95% CI: 0.69 to 0.93, p=0.003) compared with non-Hispanic White. AGE was positively associated with obesity compared with underweight and normal weight (OR=1.37, 95% CI: 1.15 to 1.62, p<0.001).Conclusion The monthly prevalence of AGE was 7.69% and showed a downward trend from 1999 to 2018 in the USA.